2020
DOI: 10.1080/17441692.2020.1801788
|View full text |Cite
|
Sign up to set email alerts
|

Gender-norms, violence and adolescence: Exploring how gender norms are associated with experiences of childhood violence among young adolescents in Ethiopia

Abstract: Adolescence is a time of particular risk for violence perpetrated by parents, teachers, peers and intimate partners. Social norms that condone violent discipline, promote masculinities focused on violence, and support gender inequality play an important role in perpetuating violence. However, little is known about the relationship between inequitable gender norms and children's experiences of violence from parents or other adults in the household. Utilising data from the Gender and Adolescence: Global Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In addition, the share of respondents who experienced physical violence in municipalities was higher than that in cities. This is in line with research in Ethiopia, but different from studies in other sub-Saharan countries and in Poland, which demonstrated a greater likelihood of urban adolescents engaging in violence than those in rural areas [ 41 43 ]. The suggestion from a previous study [ 13 ] that the prevalence of physical violence declines with age among adolescents is also supported by our results; we found that respondents in middle school (45.3%) experienced more physical violence than those in high school (32.9%).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, the share of respondents who experienced physical violence in municipalities was higher than that in cities. This is in line with research in Ethiopia, but different from studies in other sub-Saharan countries and in Poland, which demonstrated a greater likelihood of urban adolescents engaging in violence than those in rural areas [ 41 43 ]. The suggestion from a previous study [ 13 ] that the prevalence of physical violence declines with age among adolescents is also supported by our results; we found that respondents in middle school (45.3%) experienced more physical violence than those in high school (32.9%).…”
Section: Discussionsupporting
confidence: 76%
“…This outcome is different from a previous study that signalled a higher prevalence of physical violence among males, which suggests a greater social tolerance for physical violence among men [ 43 ]. We do not think this finding alone can prove that the cities and municipalities in this study have gender inequitable societies, since this would require further investigation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 'Gender-norms, violence and adolescence: Exploring how gender norms are associated with experiences of childhood violence among young adolescents in Ethiopia', Murphy et al (2020) contributed to a growing evidence base that community-level social norms can hold stronger influence over household violence against children than individual or caregiver attitudes. The study aggregated quantitative estimates of household gender norms to construct measures of community-level norms, which were strongly associated with young adolescent exposure to household physical or psychological violence.…”
Section: Introductionmentioning
confidence: 99%
“…The results highlight reductions in violence in older adolescence, possibly due to gendered shifts in social expectations for caregiver behaviours toward an adolescent girl versus boy after puberty. Other explanations include how exposure to harsh physical punishment and psychological treatment pushes some adolescent girls and boys out of the caregiver household, 'by running away, distress migration or suicide attempts' (Murphy M, 2020). Programme implications highlight the need to work at the community level to shift gender norms toward protective and preventative behavioural expectations and positive, non-violent disciplinary practices of caregivers and other adults in the household.…”
Section: Introductionmentioning
confidence: 99%